C679X loss-of-function PCSK9 variant lowers fasting glucose levels in a black South African population: A longitudinal study. (October 2018) - Chikowore, Tinashe; Cockeran, Marike; Conradie, Karin R.; van Zyl, Tertia
Abstract: Aims: To determine the longitudinal association of the loss-of-function (LOF) PCSK9 variants (C679X and A443T), proxies of PCSK9 inhibitor drugs, with LDL-C, fasting glucose and glycated hemoglobin. Methods: We conducted a five year, longitudinal study, nested within the Prospective Urban and Rural Epidemiology study, among 737 apparently healthy, male and female black South Africans of the North West province. Genotyping of the C679X and A443T PCSK9 variants was achieved using Taqman assays from Applied Biosystems. Generalized estimating equations were used to determine longitudinal association of the A443T and C679X PCSK9 variants with LDL–C, fasting glucose and glycated hemoglobin. Results: C679X and A443T variant carriers were associated with significant reductions in LDL-C of −0.98(−1.29, −0.67) mmol/L; p < 0.001) and −0.39(−0.57, −0.20) mmol/L; p < 0.001) respectively, compared to the non-carriers. Only C679X variant was independently associated with reductions in fasting glucose of −0.37 (−0.61, −0.13) mmol/L; p = 0.002) compared to non-carriers. However, the association of the selected variants with glycated hemoglobin were not significant. C679X and A443T carriers were associated with −0.07 (−0.23, 0.09) %; p = 0.400), 0.05 (−0.13, 0.22) %; p = 0.599) of glycated haemoglobin respectively. Conclusion: Our results indicated that carriers of A443T and C679X variants exhibit sustained low LDL-C levels over 5 years and have varied effects on T2D biomarkers compared to non-carriers.